Determination of phthalates in PET-packaged beverages using an MSFIA method coupled with HPLC-DAD - Jiménez Morales, Willmann A; Hinojosa Reyes, Laura; Guzmán Mar , Jorge L; Cañizares Macías, María P; Aristeo Segura, Salvador (JOURNAL OF BASIC SCIENCES, 2024)
In this work, an online preconcentration method was designed, optimized, and validated using a C18-type membrane with a Multisyrup Flow Injection Analysis (MSFIA) system coupled to HPLC-DAD equipment for the determination of contaminants derived from phthalic acid esters (DMP, DEP, and DBP) in juices stored in PET bottles. The physicochemical and hydrodynamic parameters of the method were optimized using a central composite experiment design. The method showed good precision (˂3%), a LOD of less than 0.5 μg kg–1, and a preconcentration factor of 33 times. After applying the method to 4 samples of juices, concentrations of 172.89 and 100.43 μg kg–1 of DMP and DBP were identified and quantified, respectively. Finally, recovery values that ranged between 44.12% and 141.07% were obtained for the three phthalates.